Law Enforcement Efforts against the Crime of Body Shaming Through Mediation - Elsa Intan Pratiwi (Pancasila and Law Review, 2021)
This study aims to analyze the forms of action that are categorized as body shaming crimes and criminal law enforcement against body shaming crimes on social media. This study uses a normative juridical approach. The data used is in the form of secondary data consisting of primary and secondary legal materials. The data collection method uses literature study and descriptive qualitative analysis. The results of this study indicate that, the forms of action that are categorized as body shaming crimes, namely: the words uttered contain elements of physical insult and have humiliated and lowered one's self-esteem because they can be seen/witnessed by many people, making them feel sad and depressed. Perpetrators of body shaming can be charged under Article 315 of the Criminal Code, with a maximum imprisonment of four months and two weeks or a maximum fine of four thousand and five hundred rupiahs. And if it is done on social media, the perpetrator can be charged under Article 27 paragraph (3) jo. Article 45 paragraph (3) of the ITE Law with a maximum imprisonment of four years and/or a maximum fine of seven hundred and fifty million rupiah. The police also offer a settlement process in a non-litigation context, namely by maximizing penal mediation to reduce the build up of cases in court.